Analysis Of Sheep Farming Business At Wawan Jaya Farm In Antara Village, Lima Puluh District - Nasruddin, Nanang; Kurniawan, Media Agus (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The increase in demand for livestock products in North Sumatra from year to year is increasing along with the increasing population and the increasing awareness of nutritional needs among the community. This study aims to determine the feasibility of sheep farming business in Wawan Jaya Farm Sheep Farm, Antara Village, Lima Puluh District in 2024. This research was carried out in September-November 2024 at Wawan Jaya Farm Sheep Farm, Antara Village, Lima Puluh District. The analysis method carried out is using R/C (Revenue Cost Ratio) and PP (Pay Back Period). The conclusion is based on the results of the calculation of business analysis that has been carried out on the Wawan Jaya Farm Sheep Farm. So it can be concluded that the R/C of 1.72 means that the business run by Wawan Jaya Farm is suitable for development, PP 1.80 means that the return on capital in Wawan Jaya Farm Sheep Farm is 1 Year, 08 Months.